The place of "formality" in Islamic procedure - Mahdi Hamze Howeyda (مطالعات فقه و حقوق اسلامی)
: Procedures are known by a set of formal rules and forms, and for this reason, procedures and formality are tied to each other. Today, one of the characteristics and rather the principles of procedures is its formality, in such a way that the "judicial system" cannot be imagined without the existence of formalities. The main question is, what is the relationship between formality and Islamic procedure? Is formality one of the principles, or at least one of the characteristics of Islamic procedures? A group of writers have denied the existence of any forms and formalities in Islamic procedures and on the other hand, some other most detailed issues of procedures have been considered to have a jurisprudence basis and documentation. The present article, in a descriptive and analytical way, tries to evaluate the place of this important and widely used establishment in Islamic procedure while examining the concept and basis of formalities. The result of the research shows that, due to the substantive-centered nature of the procedure, the formality in Islamic jurisprudence are not "principles" and are merely a tool for obtaining substantive rights. Therefore, Islamic procedure are considered to be one of the least formal procedures.